Cricoarytenoiditis as an Initial Manifestation of Systemic Lupus Erythematosus - Hougardy, Jean-Michel; Roper, Nicolas; Michils, Alain; Soyfoo, Muhammad S. (Case Reports in Rheumatology, 2011)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease encompassing a broadened spectrum of clinical manifestations. Vocal cords involvement in SLE is not a frequent entity but can be life threatening if not treated. We hereby report the case of a patient presenting with cricoarytenoiditis and vocal cord dysfunction revealing SLE.